2022
DOI: 10.1055/s-0042-1750331
|View full text |Cite
|
Sign up to set email alerts
|

Cancers and Benign Processes on 68Ga PSMA PET-CT Imaging Other than Prostate Cancer

Abstract: Background Imaging plays an important role in the evaluation of prostate cancer patients. In recent years, much attention has been focused on gallium 68 prostate-specific membrane antigen positron emission tomography-computed tomography (68Ga PSMA PET-CT) in prostate cancer patients and has been widely used for staging, restaging, and therapy response for these patients. The aim of this study was to report 68Ga PSMA PET-CT in other cancers and benign processes incidentally detected on 68Ga PSMA PET-CT in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…7 It also showed superiority in evaluation of hybrid synchronous histopathologies as well as patients with multiple primary neoplasms. [8][9][10] The mechanism behind the uptake and localization of PSMA by cancer cells involves the overexpression of PSMA antigen on their surface, allowing for targeted binding and internalization of PSMAtargeted agents. 11 However, the specificity of PSMA is not absolute.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 It also showed superiority in evaluation of hybrid synchronous histopathologies as well as patients with multiple primary neoplasms. [8][9][10] The mechanism behind the uptake and localization of PSMA by cancer cells involves the overexpression of PSMA antigen on their surface, allowing for targeted binding and internalization of PSMAtargeted agents. 11 However, the specificity of PSMA is not absolute.…”
Section: Introductionmentioning
confidence: 99%
“…PSMA expression has been observed in various non-prostatic malignancies, affecting its diagnostic accuracy. 10 It can also be expressed in benign conditions and can occur in postsurgical and reactive scenarios, potentially compromising the reliability of PSMA-based imaging. 10 These factors highlight the importance of cautious interpretation when relying solely on PSMA-based imaging in clinical decision making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in numerous normal tissues, for example, endometrial glands, testis, bladder, kidney tubules, pancreas islets, heart, and ganglion cells in the gastrointestinal tract and brain, weak-to-moderate levels of PSMA expression have been detected ( 9 ). Although it is reported that certain benign diseases such as lymphadenitis and malignant diseases such as lung adenocarcinoma may also exhibit PSMA uptake ( 10 ), its remarkable sensitivity and specificity for PCa continue to establish it as a dedicated imaging modality for patients with PCa. Thus, PSMA-positron emission tomography (PET) is still considered to be a rather sensitive and highly specific tool for PCa diagnosis despite its expression by subsets of various types of other tissues ( 9 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Physiological expression is also seen in renal tubules, lacrimal and salivary glands, and small intestine. [ 2 ] However, PSMA expression can also be seen in inflammation/infection, nonprostatic neoplastic cells, and nonprostatic tumor-associated neovasculature. [ 3 ] Endothelial and cytoplasmic PSMA expression is attributed to PSMA uptake in many nonprostatic tumor cells.…”
Section: Introductionmentioning
confidence: 99%